Analisis Kesulitan Belajar Mahasiswa Pada Mata Kuliah Bahasa Inggris - Fienny M Langi (Institut Agama Kristen Negeri Manado, 2020)
This study intends to analyze student learning difficulties in English language courses. This case study was conducted at IAKN Manado, specifically 30 students in the first semester of the 2019/2020 school year from 3 different study programs. Researchers use a classic and individual approach to combine data, and analyzed with qualitative descriptive methods. The results showed that students' learning difficulties occurred due to feelings of compulsion in learning, poor mastery of learning concepts, being unable to remember lessons, and not having the opportunity to practice English. Referring to the findings, it is recommended that the teacher and institutions should facilitate and provide high motivation for the learning process of English.